ANALISIS PENERAPAN METODE JARIMATIKA PADA PERKALIAN DASAR SECARA DARING DI SEKOLAH DASAR - Mukti Aulia Sari; Rossi Iskandar (STKIP Subang, 2022)
This study aims to find out how the description of mathematics learning in the application of the Jarimatika method to the online basic multiplication method in class III, and to find out how to apply the Jarimatika method to the online basic multiplication, and also to find out how the inhibiting and supporting factors for the application of the Jarimatika method to the online basic multiplication method. in class III. The subjects in this study were students of class III SDS Yasporbi III Pasar Minggu. Methods This research uses descriptive qualitative analysis. Qualitative research methods are research methods used to examine certain populations or samples, collecting data using research instruments and emphasizing aspects of in-depth understanding. The results of the study on the application of the Jarimatika method to basic multiplication online in class IIIA SDS Yasporbi III were quite well implemented, the teacher explained that using the Jarimatika method was very good, but there were still students who had not been able to apply the Jarimatika method because there were obstacles or inhibiting factors and supporting factors in the application of the method. arithmetic in basic multiplication.